Land surface evaluation for engineering practice - Griffiths, James S., Dr (Geological Society engineering geology special publication, 2001)
The volume arose out of deliberations by the Second Working Party on Land Surface Evaluation set up by the Engineering Group of the Geological Society in January 1997 and chaired by Dr. J.S. Griffiths. The book identifies examples of cost-effective methods for collecting land surface and near surface data prior to carrying further detailed ground investigations by engineering geologists, geotechnical engineers, geomorphologist and planners who have the responsibility for planning and designing potential sites of development.